Patterns of sustained e-cigarette use in a sample of young adults - Creamer, MeLisa (Addict Behav, 2018)
INTRODUCTION: E-cigarette use and devices are rapidly changing, yet there is not much scientific evidence examining these changes over time. The purpose of this study is to describe patterns of e-cigarette use in a sample of sustained (i.e., reporting past 30-day e-cigarette use at every wave) e-cigarette users over a two-year period. METHODS: Data are drawn from five waves of the Project M-PACT cohort. Analyses are limited to those reporting past 30-day e-cigarette use at each wave (n = 75). Mixed effects regressions were conducted for the following dependent variables: device type, number of days used, combustible tobacco product use, and symptoms of nicotine dependence. Each model used survey wave as the time variable, and controlled for sociodemographic variables. RESULTS: Among sustained users, the majority reported using a rechargeable device. The average number of days used was about 2 for disposable devices and 14 for rechargeable devices (p < .0001). The odds of combustible tobacco product use decreased over time (AOR = 0.71; 95% CI 0.57–0.89), while symptoms of e-cigarette nicotine dependence increased over time (β= 0.07 SE = 0.03, p-value = .02). For both e-cigarette device types, there were no changes in device type or number of days used over time. CONCLUSION: This is one of the first studies to look at changes in e-cigarette use, including symptoms of dependence and number of days used over a two-year period. This brief report extends the current literature by examining more than the prevalence and frequency of e-cigarette use.